A Conceptual Study of the Impact of UTAUT Model on the Intention and Adoption of Electronic Medical Records by physicians of Mohammed VI University Hospital Center (UHC) in Marrakech (Morocco) - Oumaima Hafide; Abdelaziz Zitouni; Youness Lafraxo (Communications of International Proceedings, 2020)
The adoption of electronic medical records in the e-Health sector in Morocco is intended to enhance hospital quality, to decrease the frequency of medical errors and to minimize the cost of health care. But few studies have focused on the predictive factors of physicians' intention to use an EMR system. Using the indicators in the UTAUT model, a theoretical model is suggested to illustrate the behavior of physicians in using an EMR system at the Mohammed VI University Hospital Center in Marrakech, Morocco.
Keywords: UTAUT model; Adoption of the Electronic Medical Records; EMR system; Mohammed VI University hospital; Marrakech (Morocco).